2017
DOI: 10.1111/jre.12492
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Role of toll‐like receptor 2 in inflammation and alveolar bone loss in experimental peri‐implantitis versus periodontitis

Abstract: Background and Objective Peri‐implantitis and periodontitis are different entities in immune characteristics even though they share similar features in clinical and radiologic signs. Toll‐like receptor 2 (TLR‐2), one of the key pathogen‐recognition receptors in the innate immune system, plays an important role in the progression of periodontitis. However, the role of TLR‐2 in peri‐implantitis remains unclear. The objective of this study was to investigate the role of TLR‐2 in inflammation and alveolar bone los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 40 publications
4
46
0
2
Order By: Relevance
“…Total RNA was isolated from cells using RNA-Bee isolation reagent (AMS Biotechnology, Cambridge, MA, USA), following the manufacturer's instructions, and subjected to reverse transcription with the Verso cDNA Synthesis Kit (Thermo Fisher Scientific) in the presence of random primers and oligo-dT. Gene expression was quantified using the LightCycler 480 SYBR Green Mouse model of ligature-induced periodontitis OC-STAMP-KO mice (The Jackson Laboratory) or wild-type (WT) mice (6-8 wk old, C57BL/J male, n = 5-6) were placed with a 5-0 silk ligature (Ethicon, Guaynabo, Puerto Rico, USA) on the upper left second molar, whereas the upper right second molar without ligature was used as a control, following the protocol that was developed by our group (12,(24)(25)(26)(27). Because we used mice raised from different breeding cages, especially those of OC-STAMP-KO strains, to avoid the effect of different oral flora, the male mice used for the experiment were cohoused for a week so that all mice harbored similar oral flora, following the protocol reported by other groups (28,29).…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from cells using RNA-Bee isolation reagent (AMS Biotechnology, Cambridge, MA, USA), following the manufacturer's instructions, and subjected to reverse transcription with the Verso cDNA Synthesis Kit (Thermo Fisher Scientific) in the presence of random primers and oligo-dT. Gene expression was quantified using the LightCycler 480 SYBR Green Mouse model of ligature-induced periodontitis OC-STAMP-KO mice (The Jackson Laboratory) or wild-type (WT) mice (6-8 wk old, C57BL/J male, n = 5-6) were placed with a 5-0 silk ligature (Ethicon, Guaynabo, Puerto Rico, USA) on the upper left second molar, whereas the upper right second molar without ligature was used as a control, following the protocol that was developed by our group (12,(24)(25)(26)(27). Because we used mice raised from different breeding cages, especially those of OC-STAMP-KO strains, to avoid the effect of different oral flora, the male mice used for the experiment were cohoused for a week so that all mice harbored similar oral flora, following the protocol reported by other groups (28,29).…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…Ligatures were removed, and the maxillae were defleshed using dermestid beetles (30). Alveolar bone resorption was measured as previously described (12,(24)(25)(26)(27)31). Briefly, the distance from the cementoenamel junction (CEJ) to the alveolar crest (AC) on the buccal side of each root was measured with a dissection microscope.…”
Section: Alveolar Bone Resorption Measurementmentioning
confidence: 99%
“…However, peri-implantitis has become prevalent accompanying the exponential growth of dental implant procedures [2,3]. Peri-implantitis is indicated by infection of implant surrounding soft tissues and bone loss, resulting in implant failure eventually [4][5][6]. The host immune and inflammatory responses caused by plaques on implant surface are crucial in the pathogenesis of peri-implantitis [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptors (TLR) are a family of wellcharacterized pattern recognition receptors (PRRs) and play an important role in the induction of pro-inflammatory cytokines by recognizing the signature molecules of the host innate immunity [25][26][27]. Our previous studies showed that TLR2 are associated with implant bone loss in a mouse model of peri-implantitis [5] and TLR4 is essential for periodontal bone loss [28,29]. In our previous study, we examined the changes of inflammatory cytokines and bone metabolism cytokines in either TLR2 only KO mice or TLR4 only KO mice [5,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed the involvement of pattern recognition receptors (PRRs), including Toll‐like receptors and C‐type lectin receptors, in the pathogenesis of peri‐implantitis. Compared with WT mice in peri‐implantitis, Toll‐like receptor 2 (TLR2) KO mice revealed significantly decreased bone loss by regulating IL‐1β, TNF‐α, and IL‐10 expression . In peri‐implant mucositis and peri‐implantitis, the recruitment of macrophages and the differentiation of osteoclast in gingival tissues may be partly induced by the enhancing of Toll‐like receptor 4 (TLR4) in gingival epithelial cells with the stimulation of titanium ions .…”
Section: Introductionmentioning
confidence: 99%